Frontline Science: A reduction in DHA‐derived mediators in male obesity contributes toward defects in select B cell subsets and circulating antibody. Issue 2 (21st December 2018) - Crouch, Miranda J.; Kosaraju, Rasagna; Guesdon, William; Armstrong, Michael; Reisdorph, Nichole; Jain, Raghav; Fenton, Jenifer; Shaikh, Saame Raza
Abstract: Obesity dysregulates B cell populations, which contributes toward poor immunological outcomes. We previously reported that differing B cell subsets are lowered in the bone marrow of obese male mice. Here, we focused on how lipid metabolites synthesized from docosahexaenoic acid (DHA) known as specialized pro‐resolving lipid mediators (SPMs) influence specific B cell populations in obese male mice. Metabololipidomics revealed that splenic SPM precursors 14‐hydroxydocosahexaenoic acid (14‐HDHA), 17‐hydroxydocosahexaenoic acid (17‐HDHA), and downstream protectin DX (PDX) were decreased in obese male C57BL/6J mice. Simultaneous administration of these mediators to obese mice rescued major decrements in bone marrow B cells, modest impairments in the spleen, and circulating IgG2c, which is pro‐inflammatory in obesity. In vitro studies with B cells, flow cytometry experiments with ALOX5 −/− mice, and lipidomic analyses revealed the lowering of 14‐HDHA/17‐HDHA/PDX and dysregulation of B cell populations in obesity was driven indirectly via B cell extrinsic mechanisms. Notably, the lowering of lipid mediators was associated with an increase in the abundance of n ‐6 polyunsaturated fatty acids, which have a high affinity for SPM‐generating enzymes. Subsequent experiments revealed female obese mice generally maintained the levels of SPM precursors, B cell subsets, and antibody levels. Finally, obese human females had increased circulating plasma cells accompanied by ex vivo B cell TNFα and IL‐10 secretion. Collectively, the data demonstrate that DHA‐derived mediators of the SPM pathway control the number of B cell subsets and pro‐inflammatory antibody levels in obese male but not female mice through a defect that is extrinsic to B cells. Abstract : DHA‐derived mediators increase select B cell subset numbers and lower circulating pathogenic IgG2c in obese male mice.